Does leadership matter in managing the village-owned enterprise? - Digdowiseiso1, Kumba; Eko Sugiyanto, Heru Dian Setiawan,; ., Suharyono (Opción, 2020)
The establishment of the village-owned enterprise (Badan Usaha Milik Desa –BUMDes), as stipulated in Law No. 6/2014 on Village, is an effort to increase economicgrowth, together with the equitable distribution of assets to the village community. It isexpected to be a pillar of economic activity in the village that serves as an institution thatremains committed to village characteristics. However, the existence of BUMDes has notfully produced satisfactory results in terms of continuation of the programs andprofitability. Therefore, this qualitative study aims to determine the factors that influencethe village head’s leadership. Using Northouse’s (2013) concept, this study finds that bothtask and relationship behaviour are very important factors to achieve success in managingBUMDes in Indonesia.